Pembatalan Perkawinan: Analisa Unsur Penipuan Mengenai Diri Pasangan dalam Perspektif Hukum Positif di Indonesia - Artanti Fitria Hassya Andrianata; Elly Nurlaili; Kasmawati Kasmawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2023)
The annulment of marriage due to misconceptions about the husband or wife is found with different reasons for the application. However, neither the Undang-Undang Perkawinan nor the KHI provides an explanation regarding the definition or elements of the misconceptions. So, it is necessary to review the laws and regulations and judges' decisions on the annulment of marriage because of misconceptions about the husband or wife, especially when there is an element of fraud, in order to provide legal certainty for the applicants and the general public. The purpose of this study examines the legal arrangements for annulment of marriage due to misconceptions that there is an element of fraud regarding the spouse according to positive law in Indonesia as well as the judge's legal considerations in granting the marriage annulment application. This research is normative juridical research, using data collection methods by means of literature studies and document studies, and processed by data processing methods, namely data selection and data classification which are then analyzed qualitatively. The results of the research and discussion explained that the annulment of marriage due to misconceptions about the couple is regulated in Pasal 27 Ayat (2) of the Undang-Undang Perkawinan and Pasal 72 Ayat (2) of the KHI. This state of misconception in the annulment of marriage occurs when there is an element of intentionality on the part of one of the parties to disguise the actual state of affairs about him by deceiving the other party. In the case of the marriage annulment judgment No. 1845/Pdt.G/2020/PA. Gsg and No. 25/Pdt.G/2020/PA. Sak, which occurs because of a misconception about husband and wife, it is known that these false elements are related to fraud. The fraud is regulated in Pasal 378 of the Kitab Undang-Undang Hukum Pidana (KUHP). The circumstances of misconception in this marriage can also be sued with an unlawful act if the act committed by one of the parties is proven to be unlawful and the act causes harm to the other party.